Trisha's table : my feel-good favorites for a balanced life - Yearwood, Trisha (Clarkson Potter, 2015)
"Hotly anticipated, and full of healthy twists on comfort food classics, Trisha's Table is bestselling cookbook author and country mega-star Trisha Yearwood's first cookbook since she slimmed down and debuted her wildly popular Food Network show, "Trisha's Southern Kitchen." Responding to an increased demand, Trisha shares how she has incorporated healthier cooking into her lifestyle without completely forgoing the induldgences she (and we all) love and crave. Trisha's Table includes a balance of healthy versions of comfort food along with a smattering of indulgences. Whether slimmed down or "original," Trisha's recipes, such as Black Bean Quinoa, Slow Cooker Georgia Pulled Pork BBQ, and Chicken Tortilla Casserole, are always delicious. Each of the more than 100 recipes will appeal to Trisha's huge southern fan base, while her fresh outlook on food and life (and her TV exposure) will also bring a new audience to this book"--